From Motherhood to Sister-Solidarity: Home-making as a Counterdiscourse to Corporate Environmental Polluting - Robert J. Hill (Adult Education Research Conference, 1998)
This presentation examines the conjunction between women-homemakers and contaminated spaces, both public and private. Learning for the women was embedded in concerns about motherhood and domesticity. Although the women never expressed their solidarity in terms of sisterhood or feminist language, they functioned as a cohesive group consciously aware of their marginalized status as women. But the "girls solidarity" was not the source of political action, rather it was the context for it. Domesticity and motherhood was a substantially stronger antecedent for action that enabled the women to build the notion that they could challenge power relations, values and beliefs of the dominant culture in the community.